Challenges Faced by Spinal Cord Injury (SCI) Patients: A Study of SCI Patients at A Public Hospital in Penang - Nurul Atikah Izzati Abdul Razak; Syazwani Drani (Asian Social Work Journal, 2022)
In Malaysia, there is a lack of published articles regarding spinal cord injury (SCI) and the roles played by social workers. Such information is important as SCI can affect the quality of life of the individual who experiences it. Indeed, SCI can be one of the most devastating injuries that a person can endure. The purpose of the study is to explore the challenges faced by SCI patients and to find out more about the relationship between SCI and social workers to enhance the quality of life of SCI patients. The study used purposive sampling in which1 10 SCI patients were selected from a Public Hospital in Penang, Malaysia. For the in-depth interviews, the study employed a semi-structured method. The findings of the study were analysed using thematic analysis. The findings identified four main challenges, faced by people suffering SCI, namely emotional challenges, physical difficulties, stigma, and a lack of facilities for disabled people. The data findings are based on the needs and demands of SCI patients.